The Implications of Sundanese Customary Law in the Character Formation of IPI Garut Students - Jamilah , Jamilah; Rahman, Maulida Aulia; Agustina, Selma Zulvia (Jurnal Pendidikan Karakter, 2025)
Education is one of the main means of character building, which aims to prepare students to become individuals who are not only intelligent but also have integrity and social responsibility. Previous research has discussed the integration of local wisdom in education, but few have focused on how the values of Sundanese customary law can specifically shape the character of university students. This study aims to fill that gap by examining how these values are interpreted, lived, and transformed into behavioral attitudes among students of IPI Garut. This study aims to explore the implications of Sundanese customary law values in shaping the character of students at Institut Pendidikan Indonesia (IPI) Garut. The research employed a quantitative associative-correlational design to determine the relationship between the understanding of Sundanese customary values and student character. Data were collected through questionnaires distributed to 316 respondents and analyzed using Pearson correlation and simple linear regression with SPSS 30 software. The findings revealed that Sundanese customary law has a positive and significant effect on character formation (r = 0.478; p < 0.001; R² = 0.229), meaning that 22.9% of the variation in student character can be explained by the understanding and application of customary law values. These values, including silih asah, silih asih, and silih asuh, are reflected in moral attitudes, social responsibility, and academic integrity. The study concludes that integrating Sundanese customary law into higher education can strengthen contextual character education rooted in local wisdom and cultural identity.